Design of an endpoint indicator for mineral resource supply risks in life cycle sustainability assessment: The case of Li‐ion batteries. (21st December 2020) - Santillán‐Saldivar, Jair; Gaugler, Tobias; Helbig, Christoph; Rathgeber, Andreas; Sonnemann, Guido; Thorenz, Andrea; Tuma, Axel
Abstract: Concerns have risen in recent years about the accessibility of raw materials considered "critical" for technological advancements. The GeoPolRisk indicator was designed as a midpoint indicator in life cycle sustainability assessment to measure geopolitical supply risk with the aim to incorporate raw material criticality as a complement to environmental life cycle assessment (LCA). A recent review of supply risk methods conducted within the Task Force on mineral resources of the Life Cycle Initiative hosted by UN Environment Programme highlighted the opportunity to extend the methodology to an endpoint level. We address this opportunity by presenting GeoPolEndpoint, an indicator that measures the socio‐economic damage of the use of mineral resources linked to the area of protection "Natural Resources" in LCA. We build upon previous efforts by introducing price elasticity considerations and modeling potential effects of supply disruptions on commodity markets in the form of a welfare loss and a loss of consumer surplus. The socio‐economic damage occurs as geopolitically driven increased costs for raw materials. We test our method on aluminum, cobalt, nickel, and copper, materials relevant for lithium‐ion batteries. Results show that nickel and cobalt dominate the contribution to socio‐economic damages because of their price and supply risk; we estimate the impact of the use of the four analyzed materials as a potential increased cost ranging from 0.30 to 1.86 USD/kWh depending on the technology and year. We build the steps to assess how the use of certain raw materials could have a substantial economic impact when developing technologies, possibly identifying the shifting of burden due to certain materials not usually deemed important from an environmental perspective. This article met the requirements for a gold‐gold JIE data openness badge described at http://jie.click/badges.